TRADE AND DIPLOMATIC RELATIONS BETWEEN BUKHARA EMIRATE AND RUSSIA IN THE XVIII-XIX CENTURIES - Akmaljanov, son of Akmaljanov Akbarjan Akmaljan; Olimova Zulfiyakhan Ibrahimjon's daughter (Journals Park Publishing, 2024)
In this article, trade relations between the Bukhara Emirate and Russia, Siberia and Orenburg trade routes, the most important sources of raw materials, the textile industry, 1755 Ernazar Maksutov's ambassadorship, 1797 Polvonkuli's ambassadorship, 1858 Colonel Ignatyev's embassy.
Keywords: mutual relations, trade routes, spun yarn, enterprises, metal products, trade security, embassy relations, Peter I, Ernazar Maksutov, Polvonkuli Gurchi, Yekaterina II, Colonel Ignatyev.